Implementation of chosen risk index during car-following behaviour under wet weather condition. (May 2019) - Shariff, M.; Puan, O. C.; Mashros, N.; Mohamed, A.; Hassan, N. A.; Ismail, C. R.; Hainin, M. R.
Abstract: This study aims to examine the effects of wet weather on accident consequence during car-following behaviours. The study analysed drivers' car-following headway on two-lane highways along passing and no passing zones associated with passenger cars and heavy goods vehicles (HGV). The speed and time gap of more than 200, 000 vehicles were recorded during dry and wet weather at 4 specific sites in Peninsular Malaysia using Automatic Traffic Counter with pneumatic tubes. Rainfall data were acquired from the nearest rain gauge station. Chosen Risk Index (CRI) was used to characterize and evaluate the accident consequence caused by wet weather incidence. The results disclose that the drivers are more cautious to avoid accident severity during wet weather compared to dry weather irrespective of vehicle type and highway features. This result is evidenced by lower CRI values during wet weather compared to dry weather. The data shows that under wet weather condition the speed that gives lower risk of accident is in the range of 47.3 to 73.9 km/h and 56.5 to 74.0 km/h i.e. which associated with CRI values in the range of 0.60 to 0.75 and 0.53 to 0.79 at passing and no-passing zones, respectively. These findings are useful for the improvement of roadway design and the implementation of traffic safety interventions.